Plant Stress Physiology 2017
DOI: 10.1079/9781780647296.0217
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation tolerance.

Abstract: Desiccation tolerance is the ability to survive loss of 90% of cellular water or dehydration to water concentrations of <0.1g HrO g-1 dry mass. It is relatively common in reproductive stru such as seeds (termed orthodox), but is rare in vegetative tissues, occurring in some 350 spe higher plants (termed 'resurrection plants'). In this chapter we present an overview of the s associated with desiccation and review the current mechanisms proposed to explain how or seeds and resurrection plants tolerate such water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Such an approach would typically take into consideration changes in the transcriptome, proteome, metabolome and lipidome, contextualised by input from biochemical, biophysical and physiological studies. To date, this has not been fully achieved for any one species, although considerable information is available for at least 12 different resurrection plant species (reviewed in Farrant et al 2012;Dinakar and Bartels 2013). Such studies have revealed common (presumably conserved) strategies among species, but yet with individual differences among them, which collectively ameliorate the stresses associated with extreme water deficit and ultimately enable a stable metabolically quiescent state in air dry tissues.…”
Section: Desiccation-tolerant Extremophytesmentioning
confidence: 99%
“…Such an approach would typically take into consideration changes in the transcriptome, proteome, metabolome and lipidome, contextualised by input from biochemical, biophysical and physiological studies. To date, this has not been fully achieved for any one species, although considerable information is available for at least 12 different resurrection plant species (reviewed in Farrant et al 2012;Dinakar and Bartels 2013). Such studies have revealed common (presumably conserved) strategies among species, but yet with individual differences among them, which collectively ameliorate the stresses associated with extreme water deficit and ultimately enable a stable metabolically quiescent state in air dry tissues.…”
Section: Desiccation-tolerant Extremophytesmentioning
confidence: 99%
“…In HDT, the leaf area exposed to light (for example) is reduced via leaf curling, the presence of reflective hairs, and anthocyanin accumulation ( Fig. 1; Challabathula et al, 2016;Farrant et al, 2017). On the other hand, under dehydration stress, PDT (see Box 1; Fig.…”
Section: Regulated Shutdown Of Photosynthesis In Poikilochlorophylloumentioning
confidence: 99%
“…The protein storage vacuoles found in orthodox seeds are thought to be very similar to the vacuoles found in resurrection plants, although the nature of the contents can differ among species ( Fig. 2; for review, see Farrant et al, 2017). For example, in the resurrection species Eragrostis Figure 2.…”
Section: Maintenance Of Cell Integrity Via the Accumulation Of (Solidmentioning
confidence: 99%
See 2 more Smart Citations